Innovative ways of studying the effect of migration on obesity and diabetes beyond the common designs: lessons from the RODAM study. Issue 1 (5th October 2016) - Agyemang, Charles; Beune, Erik; Meeks, Karlijn; Addo, Juliet; Aikins, Ama de‐Graft; Bahendeka, Silver; Danquah, Ina; Mockenhaupt, Frank P.; Schulze, Matthias B.; Klipstein‐Grobusch, Kerstin; Smeeth, Liam; Stronks, Karien
Abstract : Type 2 diabetes and obesity are major global public health problems, with migrant populations in high‐income countries being particularly affected. Type 2 diabetes and obesity are also major threats in low‐ and middle‐income countries, from which most migrant populations originate. Transitioning of societies and the resulting changes in lifestyles are thought to be major driving forces, but the key specific factors within this broad category still need to be determined. Migrant studies provide a unique opportunity to understand the potential underlying causes of these conditions, but current research is mainly geared toward analyzing the differences between migrants and the host populations in the countries of settlement. For better understanding, there is a need to extend migrant health research across national boundaries. This review discusses innovative ways of studying the effect of migration on type 2 diabetes and obesity beyond the common designs and the relevance of extending migrant health studies across national boundaries in the current era of increasing global migration. Specifically, we describe the burden and different methods for conducting migrant studies. We use the Research on Obesity and Diabetes among African Migrants (RODAM) study as a case study, discussing the methods, some results, and lessons learned, including challenges and an essential recipe for success that may guide future migrant health research.